El nuevo regionalismo en el Este de Asia (2019)
The ideas of a new regionalism arose in East Asia in the late 90s as a response to the world’s new economic scenario. This situation sets up a framework that contrasts with the strong multilateral tendencies which have historically prevailed in the region. This work aims to analyze the obstacles for the creation of a new regionalism in East Asia, the factors motivating it, and the most relevant regionalist initiatives.